Customer satisfaction towards the facility service provided in the Plaza Angsana Shopping Complex - Stam, Hazlina (2001)
Facilities Services in shopping complex was developed due to the need and satisfaction of the users. As for this, Plaza Angsana had developed facility services in order to provide services to the shoppers who come to Plaza Angsana shopping complex. The scope of this research is concentrated to five aspects of Plaza Angsana Shopping Complex i.e. building cleaning, building and mechanical & electrical equipment maintenance, safety, parking lot, and recreational facilities. Therefore, the aim of this research is to measure the degree of customer satisfaction towards the facility services provided by the Plaza Angsana shopping complex. In completing this research several limitations were faced such as limited time, data constraints and cooperation of respondents. Therefore, the study was conducted by looking at the way facility services are being performed and analyze the feedback from the shoppers who come to shopping complex. As a result, satisfaction of the users for most of the facilities provided is in average level. Thus, some suggestions are given in order to improve the facility services. Therefore the management of the shopping complex must be more efficient, so that they can fulfill the need of the customer's satisfaction.